Crystallization and preliminary X-ray analysis of the human respiratory syncytial virus nucleocapsid protein - El Omari, K. (International Union of Crystallography, 2008)
Human respiratory syncytial virus (HRSV) has a nonsegmented negative-stranded RNA genome which is encapsidated by the HRSV nucleocapsid protein (HRSVN) that is essential for viral replication. HRSV is a common cause of respiratory infection in infants, yet no effective antiviral drugs to combat it are available. Recent data from an experimental anti-HRSV compound, RSV-604, indicate that HRSVN could be the target site for drug action. Here, the expression, purification and preliminary data collection of decameric HRSVN as well as monomeric N-terminally truncated HRSVN mutants are reported. Two different crystal forms of full-length selenomethionine-labelled HRSVN were obtained that diffracted to 3.6 and ∼5 Å resolution and belonged to space group P2(1)2(1)2(1), with unit-cell parameters a = 133.6, b = 149.9, c = 255.1 Å, and space group P2(1), with unit-cell parameters a = 175.1, b = 162.6, c = 242.8 Å, β = 90.1°, respectively. For unlabelled HRSVN, only crystals belonging to space group P2(1) were obtained that diffracted to 3.6 Å. A self-rotation function using data from the orthorhombic crystal form confirmed the presence of tenfold noncrystallographic symmetry, which is in agreement with a reported electron-microscopic reconstruction of HRSVN. Monomeric HRSVN generated by N-terminal truncation was designed to assist in structure determination by reducing the size of the asymmetric unit. Whilst such HRSVN mutants were monomeric in solution and crystallized in a different space group, the size of the asymmetric unit was not reduced.